1982
DOI: 10.1161/01.hyp.4.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Behaviorally selective cardiovascular hyperreactivity in spontaneously hypertensive rats. Evidence for hypoemotionality and enhanced appetitive motivation.

Abstract: SUMMARY Spontaneously hypertensive rats (SHRs) and Wistar Kyoto controls (VVKYs) were chronically instrumented for computer-assisted recording of arterial pressure (AP) and heart rate (HR) and examined during classically conditioned emotional (fear) reactions or during the performance of a repertoire of natural behaviors, including eating, drinking, grooming, exploring, and resting. The purpose of the study was to determine whether exaggerated cardiovascular reactivity in SHRs during aversive stimulation: 1) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…4 In brief, at the time of conditioning, each rat was removed from its home cage and placed in a standard conditioning chamber enclosed by a sound attenuating cubicle. After 5 minutes of acclimation to the chamber, the tone conditioned emotional stimulus (CES) (800 Hz, 80 db, 10 sec) was presented through a speaker mounted in the chamber 40 times at an average intertrial interval of 150 seconds (range = 100-200 sec).…”
Section: Classical Fear Conditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In brief, at the time of conditioning, each rat was removed from its home cage and placed in a standard conditioning chamber enclosed by a sound attenuating cubicle. After 5 minutes of acclimation to the chamber, the tone conditioned emotional stimulus (CES) (800 Hz, 80 db, 10 sec) was presented through a speaker mounted in the chamber 40 times at an average intertrial interval of 150 seconds (range = 100-200 sec).…”
Section: Classical Fear Conditioningmentioning
confidence: 99%
“…The elevated HR is consistent with our earlier finding that resting HR is elevated in conditioned SHR relative to unconditioned SHR, which did not differ from WKY. 4 …”
Section: Resting Mean Arterial Pressure and Heart Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The WKY rat differs from the SHR not only with respect to resting blood pressure but it also displays smaller stress-induced increases in plasma cathecholamines (McCarty et al 1987), heart rate, and blood pressure (LeDoux et al 1982;Rettig et al 1986;Knardahl and Hendley 1990). In contrast, WKYs show larger endocrine and behavioral responses to stress compared not only to SHRs but also to Wistars and several other rat strains (Pare and Redei 1995).…”
mentioning
confidence: 92%
“…In contrast, a similar yet independent study demonstrated no difference in basal firing rates of VLM neurons between SHRs and WKYs (Sun & Guyenet, 1986). However in the latter study, the relationship between discharge rate of ventrolateral medullary neurons and arterial pressure was shifted towards higher pressures in SHRs compared to WKYs (Sun & Guyenet, 1986 (Hallback, 1975;LeDoux et al 1982;Yamanioto et al 1987). The specific role of the central nervous system in generating the hyperresponsiveness to various autonomic stressors is relatively unknown.…”
Section: Publication Of the Physiological Societymentioning
confidence: 82%